Left ventricular kinetic energy across heart failure subgroups and subclinical diastolic dysfunction. (3rd October 2022) - Arvidsson, P; Nelsson, A; Smith, J G; Magnusson, M; Heiberg, E; Steding-Ehrenborg, K; Arheden, H
Abstract: Background: Diastolic dysfunction is a common finding in heart failure with preserved ejection fraction (HFpEF) and is considered a key mechanism for limiting exercise performance. Meanwhile, subclinical diastolic dysfunction (SDD) without heart failure is a growing concern and may be common in the general population [1, 5[. The kinetic energy (KE) of intracardiac blood flow reflects the work spent on accelerating blood [3] and may provide a novel window into diastolic filling dynamics [2, 4]. Our aim was therefore to quantify left ventricular KE in HFpEF patients and compare with healthy controls, subjects with SDD, and heart failure patients with moderately reduced (HFmrEF) or reduced ejection fraction (HFrEF). Methods: We studied 12 healthy controls, 22 healthy subjects with 1–2 echocardiographic criteria of diastolic dysfunction (SDD), 16 HFpEF, 9 HFmrEF, and 16 HFrEF patients. All subjects underwent CMR imaging at 1.5T with acquisition of anatomical cines and 4D flow from a box covering the heart. The LV was delineated over the cardiac cycle and KE inside the segmentation calculated as 0.5 × m × v2, where v is the instantaneous velocity vector magnitude and m is blood mass. Group comparisons of peak and average values were performed using Kruskal-Wallis test with Dunn's uncorrected post hoc test. Significance was assigned at p<0.05. Median values are given. Results: Groups were similar with regard to sex, blood pressure, and body surface area. HFpEF (median 72 years) and HFrEF patients (67 years) were significantly older than subjects with SDD (62 years, p=0.001). Examples of KE are shown in Fig. 1. Systolic peak and average KE did not differ between groups (p=0.81 and p=0.54 respectively, Fig. 2). Diastolic peak KE was higher in all groups of heart failure compared to controls (p<0.03 for all) and diastolic average KE was higher in HFmrEF and HFrEF compared to controls (p<0.02). The standard deviation for SDD was wider than in controls (1.6 mJ vs 0.8 mJ for systolic peaks, 2.7 mJ vs 1.1 mJ for diastolic peaks) and more closely resembled the HFpEF group (2.1 mJ in systole, 2.3 mJ in diastole). Conclusions: Systolic kinetic energy expenditures are on average similar between controls, subjects with subclinical diastolic dysfunction, and heart failure patients, indicating that cardiac pumping involves approximately the same amount of systolic acceleration for a given afterload. Conversely, diastolic KE was found more dispersed both in heart failure and in asymptomatic individuals with subclinical diastolic dysfunction. Higher peak values of KE were seen in diastole for all types of heart failure including HFpEF, indicating more work is spent filling the ventricle. Measurements of KE in diastole could potentially be a new tool for assessment of heart failure, including early stages of disease development in some individuals with subclinical diastolic dysfunction. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart Lung FoundationRegion of Scania, Sweden